Complete nothing - Scott, Kieran, 1974- (Scott, Kieran, 1974- True love novel, 2014)
True, also known as Eros, the Goddess of Love, tries to bring together a second pair of soul mates in her quest to return to Olympus and be reunited with her own true love, Orion.